114k views
4 votes
HES
LO)
What is the solution to the equation -(5-(a+1)) = 9-(5-(2-3))?
TESI

1 Answer

1 vote

Solution for given equation -(5-(a+1)) = 9-(5-(2-3)) is a = 7

Solution:

Need to determine solution of following equation’

-(5-(a+1)) = 9-(5-(2-3))

Means need to solve the above equation for "a"

On solving operation in most internal bracket we get

-(5-(a+1)) = 9- ( 5 – ( -1))

On opening inside brackets we get,

-(5 – a – 1 ) = 9 – ( 5 +1 )

On solving remaining brackets we get

-5 + a + 1 = 9 – 6

=> a – 4 = 3

=> a = 4 + 3 = 7

=> a = 7

Hence solution for given equation -(5-(a+1)) = 9-(5-(2-3)) is a = 7

User Danronmoon
by
5.4k points